The influence of heavy work investment on work outcomes in the hospitality industry in Serbia - Slobodan Čerović; Ivana Blešić; Jelena Tepavčević; Svetlana Vukosav; Vuk Garača; Milan Bradić (Amfiteatru Economic Journal, 2020)
HWI is a phenomenon influencing individuals, their families, workplaces and society. The phenomenon is evidently present, especially among hospitality employees. The model proposed in this study included two fundamental sub-dimensions of HWI (time and effort) and its relationship with antecedents and outcomes. Data was gathered from 180 hospitality employees (hotels and restaurants) in Serbia. Taking several previous types of research as a basis, HWI (Work Investment and Time Commitment) was used as a mediational mechanism between antecedents and work outcomes of HWI. Hypotheses tested the relationships between constructs as well as the mediational role of HWI between antecedents and work outcomes. The results showed that HWI-WI is a full mediator of the relationship between work engagement and turnover intention, workaholism-WE and job satisfaction, and between workaholism-WC and job satisfaction. In the case of HWI-TC, the full mediated effect was confirmed in a relationship between work engagement and intent to leave the organization, workaholism-WC and job satisfaction as well as between workaholism-WC and job burnout. Theoretical and practical implications are discussed in the study.
Keywords: J24; J63; L83; Z31; 330; hospitality; heavy work investment; workaholism; work engagement; job burnout; turnover intentions